Gender Culture and Gender Gap in Employment - Pamela Campa; Alessandra Casarico; Paola Profeta (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper analyzes to what extent gender culture affects gender gap in employment. Drawing on Italian data, we measure culture by building two indices: one based on individual attitudes, as done in the existing literature; one based on firms' attitudes. Firms' beliefs, which express their set of ideas, values and norms, though generally neglected, are as important as individuals' attitudes to explain female labor market outcomes. Using an instrumental variable analysis, we show that our index of gender culture based on firms' attitudes is significant in explaining gender gap in employment in Italian provinces. We show that the same holds when culture is measured with reference to individual attitudes.
Keywords: J16; 330; firm's culture; Italian provinces; instrumental variable; Geschlecht; Soziale Werte; Unternehmenskultur; Geschlechterdiskriminierung; Arbeitsmarktdiskriminierung; Provinz; Italien